Metagenomic evidence for antibiotic-associated actinomycetes in the Karamay Gobi region - Yang, Shuai; Zhang, Wei; Yang, Bo; Feng, Xin; Li, Yiyang; Li, Xiaolin; Liu, Qin (Frontiers in Microbiology, 2024)
Due to the misuse of antibiotics, there is an increasing emergence, spread, and human health crisis of multidrug-resistant (MDR) bacteria. To address clinical antibiotic resistance and prevent/control pathogenic microorganisms, the development of novel antibiotics is expected. This also offers a new approach to discovering valuable actinobacterial flora capable of producing natural bioactive products. In this study, we employed bioinformatics and macro-genome sequencing to collect 15 soil samples from three different locations in the Gobi region of Karamay. Firstly, we assessed the diversity of microorganisms in soil samples from different locations, analyzing the content of bacteria, archaea, actinomycetes, and fungi. The biodiversity of soil samples from outside the Gobi was found to be higher than that of soil samples from within and in the center of the Gobi. Secondly, through microbial interaction network analysis, we identified actinomycetes as the dominant group in the system. We have identified the top four antibiotic genes as Ecol_fabG_TRC, Efac_liaR_DAP, tetA(58), and macB by CARD. These genes are respectively associated with peptide antibiotics, disinfecting agents and antiseptics, tetracycline antibiotics, and macrolide antibiotics. In addition, we also obtained 40 other antibiotic-related genes through CARD alignment. Through in-depth analysis of desert soil samples, we identified several unstudied microbial species belonging to different families, including Erythrobacteriaceae, Solirubrobacterales, Thermoleophilaceae, Gaiellaceae, Nocardioidaceae, Actinomycetia, Egibacteraceae, and Acidimicrobiales. These species have the capability to produce peptide antibiotics, macrolide antibiotics, tetracycline antibiotics, as well as disinfectants and preservatives. This study provides valuable theoretical support for future in-depth research.